Community Participation in Education Experiments and Experiences Under People's Planning Campaign in Kerala - P.K. Michael Tharakan
To interpret good government as a result of circumstances lying within the control of the typical agency manager or division chief, in sum, poses a particular challenge. It requires that such experiences be unearthed, pored over, and interpreted back accurately to those who invent advice. This will enable inadvertency to be turned into intention the next time around. To draw attention to achievements that government are not noticing or not repeating, then, is not to dismiss them to the contrary. It is a way of showing what governments are already capable of doing. This, after all, is how an edifice of good advice should be built.